Perceptions of Online Newspapers on Adolescent Pregnancy in Malaysia - Razali, Salmi; Jaris, Nur Hidayah; Sham, Fatimah; Daud, Suzanna; Badeshae , Semran Kaur (Advances in Humanities and Contemporary Studies, 2021)
Adolescent pregnancy is an essential social and health issues in Malaysia.  Local online newspapers have published substantial articles on this phenomenon. However, little scholarly discussion on how and what has been presented by online newspaper articles to the public about adolescent pregnancy. This study aimed to describe the perspective of online newspapers on adolescent pregnancy. Data were retrieved from 8 local online newspapers. The selection criteria include any articles, such as highlights, commentary, opinion, letter, report or photo that described the phenomenon of adolescent pregnancy in Malaysia. Article published from January 2000 to October 2020 were included. The articles were retrieved, discussed and analysed using framework analysis. Matrices of emergent themes were developed following the questions guide. Online newspapers might misrepresent the actual occurrence of adolescent pregnancy in Malaysia. The contributing factors to adolescent pregnancy in this country include misuse of media and information technology, poor parenting and family support, lack of knowledge on sexuality, poor accessibility for contraception and association of adolescent pregnancy with sexual violence against girls. The main consequences were physical and psychological problems, social exclusion and infant abandonment. Interventions include proper parenting style, sexuality education and implementation of special programs to address adolescent pregnancy. The public can learn much knowledge about adolescent pregnancy from online newspapers which function as a beneficial medium for the dissemination of knowledge.